Language education policy and practice in East and Southeast Asia. (14th March 2017) - Kirkpatrick, Andy; Liddicoat, Anthony J.
Abstract : East and Southeast Asia represents a linguistically and culturally diverse region. For example, more than 700 languages are spoken in Indonesia alone. It is against this backdrop of diversity that the ten countries that comprise Association of South East Asian Nations (ASEAN) have recently signed the ASEAN Charter which, while calling for respect for the region's languages, cultures and religions also officially nominates English as ASEAN's working language. In this article, we examine the language education policies of the region and consider the implications of these policies for the maintenance of linguistic and cultural diversity on the one hand and the promotion of English and the respective national languages on the other. As ASEAN is closely connected to the three major countries of China, Japan and South Korea, as indicated by the 'ASEAN + 3' forum, we also include these countries here. We stress that, as space forbids an in-depth treatment of the language education policies of each of the 13 countries, we have chosen to describe and discuss in some depth the policies of 5 countries (China, Indonesia, Japan, the Philippines and Vietnam), as these provide a cross-section of language policy contexts and approaches in the region. We add brief notes on the policies of the remaining countries.